Earnings disclosures and stockholder lawsuits - Skinner, Douglas J. (Journal of Accounting and Economics, 1997)
This paper provides evidence on whether managers can reduce stockholder litigation costs by disclosing adverse earnings news ‘early’. Inconsistent with this idea, I find that voluntary disclosures occur more frequently in quarters that result in litigation than in quarters that do not. However, this result occurs because managers' incentives to predisclose earnings news increase as the news becomes more adverse, presumably because this reduces the cost of resolving litigation that inevitably follows in bad news quarters. After controlling for these incentives using estimated stockholder damages, I find some evidence that more timely disclosure is associated with lower settlement amounts.